Analysis of Risk Factors for Gestational Hypertension in Pregnant Women of the II And III Trimesters in the Coastal Area East Flores District - Lamak, Maria R.J.; Nayoan, Christina R; Weraman, Pius (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
Introduction: Gestational hypertension is a condition in which blood pressure in pregnant women increases up to 140/90 mmHg or more for the first time at the 20 weeks of gestation, without a history of hypertension before pregnancy and no proteinuria. This study aimed to analyze the risk factors for gestational hypertension in pregnant women during the second and third trimesters who lived in the coastal areas of East Flores Regency.Method: Case-control studies were used in this study. Total the case group in this study was 16 mothers, while the control group was 16 mothers. Data were analyzed using a Chi-Square test.Results: The results of the analysis showed there are significant relationships between the age of mothers (p=0.000), parity (0.000), and the history of long-use of contraception (p=0.000 with the incidence of gestational hypertension in pregnant women in the second and third trimesters in the coastal area of East Flores Regency). The most dominant and significant variable causing gestational hypertension in pregnant women during the second and third trimesters was parity (OR=22.075; 95% CI: 0.712-684.613). However, the study also found there is no relationship of gestation hypertension with consumption of foods containing saturated fat, consumption of salty foods, fruit consumption and vegetables, coffee drinking habits, ANC visits, family support, and obesity.Recommendation: It is important for the health workers to increase mother’s knowledge and communities’ awareness about age at risk and parity at risk. Thus, health providers should carry out more routine monitoring and provide counseling about 4 important factors in planning pregnancy.